Conservation impacts of commercial cultivation of endangered and overharvested plants. Issue 2 (26th November 2018) - Liu, Hong; Gale, Stephan W.; Cheuk, Mang Lung; Fischer, Gunter A.
Abstract: Overharvesting is one of the greatest threats to species survival. Farming overharvested species is a conservation strategy that can meet growing market demand and conserve wild populations of the target species. This strategy is compatible with the international community's desire to uphold the right of local communities to use biological resources to support their livelihoods. However, studies investigating whether farming can alleviate poaching pressure have focused almost exclusively on animals. To address the shortfall in plant‐focused studies, we compiled information on commercial cultivation of threatened plants to assess its conservation benefits. Because China's rising middle class has rapidly intensified demand for wildlife products, we searched the scientific literature published in Chinese (China National Knowledge Infrastructure and Baidu) and in English. We found 32 reports that contained data on 193 internationally or nationally threatened plant species that were under commercial cultivation. These reports showed that cultivations of 82% of the 193 species were sustained by collecting whole plants from the wild periodically or continuously. Although based on a small sample size, species that were maintained in cultivation only through artificial propagation or seeds collected in the wild were likely associated with a reported reduction in wild harvesting of whole plants. Even so, results of correlation analyses suggested that production system, scale, and when a species began being cultivated had little effect on conservation status of the species, either globally or in China. However, species brought into cultivation relatively recently and on a smaller scale were more likely to have undergone a reduction in collecting pressure. Farming of nonmedicinal plants was most problematic for species conservation because wild plants were laundered (i.e., sold as cultivated plants). For effective conservation, policy to guide cultivation operations based on the target species' biological characteristics, cultural significance, market demand, and conservation status is needed. Abstract : Article impact statement : Cultivation of overharvested plants may not benefit conservation; multiple stakeholders with different expertise are needed to ensure it does.